A new device to select carriers for biomass immobilization and application in an aerobic/anaerobic fixed-bed sequencing batch biofilm reactor for nitrogen removal - Sarti, A. [UNESP]; Lamon, A. W.; Ono, A.; Foresti, E. (IWA Publishing, 2016)
This study proposes a new approach to selecting a biofilm carrier for immobilization using dissolved oxygen (DO) microsensors to measure the thickness of aerobic and anaerobic layers in biofilm. The biofilm carriers tested were polyurethane foam, mineral coal (MC), basaltic gravel, and low-density polyethylene. Development of layers in the biofilm carrier surface was evaluated using a flow cell device, and DO profiles were conducted to determine the size of the layers (aerobic and anaerobic). MC was the biofilm carrier selected due to allowing the development of larger aerobic and anaerobic layers in the biofilm (896 and 1,058 ?m, respectively). This ability is supposed to improve simultaneous nitrogen removal by nitrification and denitrification biological processes. Thus, as a biofilm carrier, MC was used in a fixed-bed sequencing batch biofilm reactor (FB-SBBR) for treatment of wastewater with a high ammonia concentration (100-400 mgNH4-N L1). The FB-SBBR (15.0 L) was filled with matrices of the carrier and operated under alternating aeration and non-aeration periods of 6 h each. At a mean nitrogen loading rate of 0.55±0.10 kgNH4-N m3 d1, the reactor attained a mean nitrification efficiency of 95±9% with nitrite as the main product (aerobic period). Mean denitrification efficiency during the anoxic period was 72±13%.
Keywords: Biofilm thickness; Intermittent aeration; Microsensor; Mineral coal; Sequential batch reactor